THE ROLE OF GLOBALISATION IN CLIMATE CHANGE POLICY (Multidisciplinary Journal of Science and Technology, 2025)
Globalization has had a significant impact on climate change policy through increased international cooperation, technology transfer, and increased awareness of environmental issues. However, it has also contributed to global environmental degradation through increased industrial activity, deforestation, and carbon emissions. This article examines the dual role of globalization in climate change policy, analyzing its positive and negative impacts. It examines the impact of global governance institutions, the role of transnational corporations, and the effectiveness of international agreements such as the Paris Agreement. Finally, the article discusses potential solutions for reconciling globalization with sustainable environmental policies.